Procedure of the of un security council - "Bailey, sydney D." (Oxford, 1988)
The Procedure of the UN Security Council is the definitive book of its kind and has been widely used by UN practitioners and scholars for over twenty years. This new revised and thoroughly updated third edition encompasses the many changes in Council procedure that have occurred since the end of the Cold War. While retaining pertinent historical material from previous editions the book contains new text, tables and appendices on the following issues: * The appointment of the UN Secretary-General * The relationship with the International Court of Justice and the General Assembly * The veto and Security Council membership * Chapter VII resolutions, UN peace-keeping and UN-authorized enforcement * Developments in the sanctions committees and other subsidiary organizations * De jure and de facto Charter amendments * Informal Consultations, private and 'Arria formula' meetings * Relations with non-members and troop contributors, including transparency, Presidential briefings and orientation debates * The Provisional Rules of Procedure * Changes in Council documentation * The Provisional Rules of Procedure * Changes in Council documentation
Keywords: Security council